Efektivitas program bantuan operasional sekolah dalam meningkatkan akses pendidikan - Sahila, Hilaliyah; Maesaroh, Siti; Baharuddin (Program Studi Magister Pendidikan Agama Islam, 2024)
Education is one of the factors that influences development in a country, including Indonesia. The Indonesian nation's commitment to education, is confirmed in the Constitution of the 45 Constitution, Article 31, which guarantees the right to education for every citizen. This constitutional basis was then translated into government policy, one of which was the School Operational Assistance Program (BOS) which was launched in 2005. The BOS program aims to provide the widest possible access to education for every level of Indonesian society in order to realize equitable and quality education. The aim of this research is to analyze the effectiveness of the School Operational Assistance program in increasing access to education. This research method is a library research with a descriptive qualitative approach. The research results show that the school operational assistance program has proven effective in increasing access to education for all Indonesian people. The school operational assistance program has proven effective in increasing access to education for all Indonesian people. Abstrak Pendidikan merupakan salah satu faktor yang memengaruhi pembangunan dalam suatu negara, tidak terkecuali Indonesia. Komitmen pendidikan bangsa Indonesia, ditegaskan dalam konstitusi UUD’45 Pasal 31, yaitu menjamin hak mendapatkan pendidikan tiap warganya. Landasan konstitusional tersebut kemudian diterjemahkan ke dalam kebijakan pemerintah, salah satunya Program Bantuan Operasional Sekolah (BOS) yang diluncurkan tahun 2005. Program BOS bertujuan untuk memberikan akses pendidikan seluas-luasnya bagi tiap lapisan masyarakat Indonesia guna mewujudkan pendidikan yang berkeadilan dan bermutu. Tujuan penelitian ini untuk menganalisis efektivitas program Bantuan Operasional Sekolah dalam meningkatkan akses pendidikan. Metode penelitian ini merupakan studi kepustakaan (library research) dengan pendekatan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa program bantuan operasional sekolah terbukti efektif meningkatkan akses pendidikan bagi seluruh rakyat Indonesia. Program bantuan operasional sekolah terbukti efektif meningkatkan akses pendidikan bagi seluruh rakyat Indonesia.